Systematic Literature Review: Dukungan Sosial sebagai Pilar Kesejahteraan Psikologis Lansia - Fathiyah, Amya Bunga; Seniati, Ali Nina Liche (Jurnal Psikologi Perseptual, 2025)
The increasing number and proportion of the elderly population in Indonesia, reaching one in 10 Indonesians, has led to various challenges, including economic slowdown, demographic imbalance, limited adoption of healthy lifestyles, and a higher risk of depression. Additionally, older adults must cope with physical, social, and emotional changes associated with aging. This phenomenon is a global concern, as their psychological well-being is strongly influenced by the quality of social support they receive. This study integrates previous findings to provide a comprehensive understanding of the role of social support in enhancing elderly psychological well-being. Using a systematic literature review, the selection process from JSTOR and Scopus databases resulted in 10 relevant articles. The synthesis identified three key themes: (1) the function of social support in psychological well-being, (2) mechanisms for improving psychological well-being, and (3) sources of social support influencing psychological well-being. By integrating insights from multiple sources, this review highlights the impact of social support in mitigating the negative effects of aging and improving elderly well-being. These findings are expected to serve as a foundation for more effective interventions and policies to enhance the psychological well-being of older adults, particularly in addressing the challenges posed by an aging population. Peningkatan jumlah dan proporsi penduduk berusia lanjut di Indonesia yang berada pada angka satu dari 10 orang penduduk Indonesia menimbulkan berbagai masalah, seperti perlambatan ekonomi, ketidakseimbangan demografi, hingga meningkatnya risiko depresi. Selain itu, mereka juga harus menghadapi perubahan fisik, sosial, dan emosional akibat penuaan. Fenomena ini menjadi perhatian global, terutama karena kesejahteraan psikologis lansia sangat dipengaruhi oleh kualitas dukungan sosial yang mereka terima dari lingkungan sekitar. Penelitian ini bertujuan untuk mengintegrasikan temuan terdahulu untuk memberikan gambaran holistik mengenai peranan dukungan sosial dalam mendukung kesejahteraan psikologis lansia. Dengan menggunakan metode systematic literature review, proses seleksi berbagai artikel dari database JSTOR dan Scopus menghasilkan 10 artikel yang memenuhi kriteria relevansi. Hasil sintesis menunjukkan bahwa terdapat tiga tema utama mengenai bagaimana dukungan sosial berkontribusi pada peningkatan kesejahteraan psikologis lansia, yaitu: (1) fungsi dukungan sosial terhadap kesejahteraan psikologis; (2) mekanisme peningkatan kesejahteraan psikologis; dan (3) sumber dukungan sosial yang memengaruhi kesejahteraan psikologis. Dengan mengintegrasikan wawasan dari berbagai sumber, hasil tinjauan literatur ini berdampak pada peningkatan kesadaran akan pentingnya memperkuat jaringan sosial lansia guna meningkatkan kesejahteraan psikologis mereka di hari tua. Temuan ini diharapkan menjadi acuan bagi intervensi yang lebih efektif dalam meningkatkan kesejahteraan psikologis lansia di masa depan, khususnya dalam menghadapi fenomena penuaan penduduk.